Developing and validating a model explaining the assimilation process of RFID: An empirical study. - Hossain, M.; Quaddus, Mohammed; Islam (Springer, 2014)
In this research we studied the assimilation process of a technological innovation (i.e. technovation) called Radio Frequency Identification (RFID). Like many other technovations, RFID is considered as a revolutionary one, but its assimilation is an evolutionary process. Here, we extended the conventional assimilation theories and initiated an intellectual argument by introducing extension as an important stage of assimilation, which is contextual and highly relevant for RFID assimilation process. Data for the empirical tests were collected via survey from 221 livestock farms in Australia that are using RFID for livestock identification and tracing. We examined ten Technology-Organization-Environmental (TOE) factors on four stages of RFID assimilation process. Empirical results, based on Partial Least Square (PLS)-based Structural Equation Modelling (SEM), suggest that assimilation of RFID technovation does involve four stages: initiation, adoption, routinization, and extension. We also found that one single factor may have different effect on different stages of assimilation, which may even be different directioned. For instance, external environmental uncertainty has a positive impact on RFID adoption while it has a negative impact on RFID extension. The paper discusses the results and practical implications in detail. © 2014 Springer Science+Business Media New York.